2015
DOI: 10.1093/gerona/glv169
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular Lipid and Impaired Myofiber Contraction in Normal Weight and Obese Older Adults

Abstract: These data indicate that greater intramyocellular lipids are associated with slower myofiber contraction, force, and power development in obese older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
155
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 32 publications
(32 reference statements)
19
155
1
Order By: Relevance
“…This finding, along with the lack of reduced muscle mass at day 10, suggest that atrophy does not account for the loss of muscle function in old mice at day 10. Further histological evaluation of soleus muscle in ALI mice revealed increased intramyocellular lipid (IMCL) droplet size in old versus young ALI mice at day 10 in both type I and type II myofibers (Figure 1K), a finding associated with both impaired skeletal muscle function (Choi et al 2016; Picard et al 2012) and metabolism (Consitt et al 2009) in previous studies.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…This finding, along with the lack of reduced muscle mass at day 10, suggest that atrophy does not account for the loss of muscle function in old mice at day 10. Further histological evaluation of soleus muscle in ALI mice revealed increased intramyocellular lipid (IMCL) droplet size in old versus young ALI mice at day 10 in both type I and type II myofibers (Figure 1K), a finding associated with both impaired skeletal muscle function (Choi et al 2016; Picard et al 2012) and metabolism (Consitt et al 2009) in previous studies.…”
Section: Resultssupporting
confidence: 52%
“…While the mechanistic link between the metabolic changes seen in old mouse muscle and the reduction in muscle contractile force are not fully elucidated in this study, we find increased size of intramyocellular lipid droplets in old ALI muscle at day 10. Other studies have found an association between intramyocellular lipid accumulation and impaired muscle contractility in mice and humans (Choi et al 2016; Duval et al 2007; Picard et al 2012; Pugh et al 2013), though the mechanisms underlying this association remain unclear.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Undernutrition is a powerful risk factor for sarcopenia (4,23) and might well explain the increased prevalence of sarcopenia in patients with lower BMI levels. On the other hand, although sarcopenia often coexists with elevated BMI, a condition referred to as sarcopenic obesity (24), it has been demonstrated that compared to normal weight individuals, obese subjects have greater thigh muscle volume, increased crosssectional area of type I skeletal muscle fibers, increased muscle lipid content (25), and a lower muscle quality (26).…”
Section: Discussionmentioning
confidence: 99%
“…Intramyocellular lipid and ectopic adipocytes are found in a range of conditions with decreased muscle mass and strength, including aged muscle, 98 disuse, 99 and muscular dystrophies, such as Duchene muscular dystrophy (DMD). 100 Fatty muscle has also been identified in the pathogenesis of obesity 101 and linked to poor muscular mechanical properties 102 and insulin resistance. 103 Importantly, myosteatosis accelerates with age, and fatty infiltration in the thigh muscle is associated with increased risk of hip fracture in the elderly.…”
Section: Impact Of Obesity On Musculoskeletal Tissue Systemsmentioning
confidence: 99%